Pengembangan Kewirausahaan Berbasis Pengelolaan Sampah Melalui Pemanfaatan Aplikasi Teknologi Informasi (Program UKM Indonesia Bangkit) - Hendra Jaya; Ilham Thaief; Iwan Suhardi; Satria Gunawan (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. The Indonesian UKM Bangkit Program is one of the programs implemented by the Directorate for Research and Community Service, Deputy for Research and Development, Ministry of Research and Technology / National Agency for Research and Innovation for the 2020 Fiscal Year. Rise up by innovating to support Small and Medium Enterprises (UKM) / Small and Medium Enterprises and Cooperatives (UKMK) in running a less contact economy to support the economy to remain productive during the COVID 19 pandemic by prioritizing database-based information technology in the era of the Industrial Revolution ( RI 4.0). This implementation method is the result of an agreement between the Proposer and the Assisted Village and the village partner group is the management of plastic waste waste using the concept of a Waste Bank that is integrated with IT (smartphone-based and Internet of Things-IoT). To achieve its objectives, the activities of UKM Indonesia Bangkit Desa Aeng Batu-batu Kec. Galesong Utara District. Takalar. The method used for the implementation of this activity is the participatory community empowerment method with the Participatory Rural Apraissal model, which is an approach method in the process of empowering and increasing community participation, which emphasizes community involvement in all activities carried out. The concept of a Waste Bank based on Information Technology (using a Smartphone Application and based on IoT (internet of Things) can make it easier for residents. Weighing equipment is placed into the homes of customers who are part of the "BANK WASTE" organization. This tool is placed in every resident's house. plastic is already in the position of transportation, then the officer will carry out the transportation of waste to be used as balance.